Implementasi Aplikasi Sistem “Pakar Anggrek” Berbasis Android Di Kebun Raya Liwa - Mahfut; Admi Syarif; Tundjung Tripeni Handayani; Sri Wahyuningsih; Kurnia Muludi; Muhammad Irfan Ardiansyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Natural orchids are one of the original flora collections in Liwa Botanical Gardens that need to be preserved. Based on the results of our previous research, it is known that some natural orchids show symptoms of disease infection. The Liwa Botanical Gardens do not yet know a safe disease infection control technique. Disease control is still using pesticides that are harmful to the environment. The results of our previous research have resulted in new methods and solutions for disease control through a web-based expert system. This method was considered very helpful for diagnosis but was considered inefficient, so the Android-based "Orchid Expert" application was developed. This Community Service Dissemination of Research Results (PKM-DHR) activity is a continuation of our previous research results. The problem-solving formulation method is carried out through direct counselling and training at the Liwa Botanical Gardens. The activity was carried out on Wednesday, August 16, 2023, with a total of 30 participants. The results of the training activities at the demonstration stage of downloading and using the application show that the accuracy of the system diagnostic results is valid, with an accuracy rate of 92.9%. This can be interpreted as meaning that this application can be applied in society. The results of this activity indicate that the Liwa Botanical Garden management understands and is able to apply the development of natural orchid disease control methods as a conservation effort. Furthermore, the Liwa Botanical Garden is also expected to be able to independently diagnose and control natural orchid disease infections.